Structural and transport phenomena of urocanate‐based proton carrier in sulfonated poly(ether ether ketone) membrane composite. Issue 24 (29th October 2018) - Nimmanpipug, Piyarat; Kodchakorn, Kanchanok; Lee, Vannajan Sanghiran; Yana, Janchai; Jarumaneeroj, Chatchai; Phongtamrug, Suttinun; Chirachanchai, Suwabun
ABSTRACT: Proton transport is one of crucial phenomena in electrolytic part highly considered to overcome a limit in fuel cell efficiency improvement. Proton conducting organic electrolyte was modeled and simulated at atomistic level of calculation by doping of butyl urocanate (C4U), a composite material with imidazole substructure, with sulfonated poly(ether ether ketone) (SPEEK) amorphous membrane at various working temperature. Molecular dynamics simulations were used to investigate structural and dynamics characteristic of C4U in the membrane comparing with the SPEEK‐hydronium membrane model as a control. From simulations, thermal effect on water and proton carriers cluster surrounding the sulfonate groups was explored. At higher temperature, the more transport dynamics of C4U ions in SPEEK membranes were found than that of hydronium ions in the control system. Likewise, phase separation of hydrophobic and hydrophilic parts was taken into consideration here. A critical role of the enhancing proton conductivity by increasing the diffusion coefficient at temperature beyond C4U melting point in composite polymer membrane was emphasized. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1625–1635 Abstract : A designed additive material with imidazole substructure to enhance proton conductivity in a polymer electrolyte membrane fuel cell at high working temperature was verified. The diffusion coefficient of butyl urocanate (C4U) in sulfonated poly(ether ether ketone) (SPEEK) can be enhanced with increasing temperature. The effect of doped C4U on the structure and dynamics of SPEEK was evaluated using molecular dynamics simulations. Structure, transport dynamics, and thermal effect on water and proton carrier clusters surrounding the sulfonate groups were explored.